The importance of sulfur and oxygen for living organisms and plants - Xoliqulov Hamro Jasur o‘g‘li; Pardayev Ulug'bek Xayrullo o'g'`li; Tilyabov Maxsudjon Umurzokovich, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
the acquisition of sulfur, oxygen and phosphorus, the wider application of properties and properties. Acquaintance with new information, mastering the available information. Interpretation and strengthening of data from developed countries. Recommendations and suggestions on the importance of conditions for the development and rise of plants(flowers).